"I" on You: Identity in the Dictator Game - Anita Kopányi-Peuker; Jin Di Zheng (Tinbergen Institute, 2019)
We study a giver's generosity depending on her relationship with the recipient and the observer. We assign different group identities to the players using a variation of the minimumgroup paradigm, and test the effect of group memberships on altruistic giving in the dictator game with a passive observer. The results show that the dictator gives the least when she is from a different group than the other two. We further show that dictators give more when there is no observer. This is driven by male subjects who react more to the presence of the observer.
Keywords: D91; C72; C92; 330; dictator game; observer; group identity; laboratory experiment